2019
DOI: 10.1155/2019/4217057
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Alternative Medicine Use in Amyotrophic Lateral Sclerosis Cases in South Korea

Abstract: Patients with amyotrophic lateral sclerosis (ALS) sometimes consider complementary and alternative medicine (CAM) because of ineffective treatment. This study investigated the prevalence and utilization pattern of CAM among patients with ALS in South Korea. Participants were recruited through homecare services for mechanical ventilation in South Korea. This study comprised a face-to-face cross-sectional survey with staff members available to address any queries. Fifty-five participants were included; all had u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…Similarly, Yu et al [5] and Baek et al [31] showed that the mean ΔFS was 0.73-0.75, and the mean ALSFRS-R score was 35-37. The average age of symptom onset was also 50.7-55.9 in the other Korean studies [31,32], which was similar to 54.6 years in the present study. Additionally, the rate of events, including PEG, tracheostomy, and death, was 57.8%, which was similar to the 61.0% result in the previous study [5].…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, Yu et al [5] and Baek et al [31] showed that the mean ΔFS was 0.73-0.75, and the mean ALSFRS-R score was 35-37. The average age of symptom onset was also 50.7-55.9 in the other Korean studies [31,32], which was similar to 54.6 years in the present study. Additionally, the rate of events, including PEG, tracheostomy, and death, was 57.8%, which was similar to the 61.0% result in the previous study [5].…”
Section: Discussionsupporting
confidence: 90%
“…A high percentage (n = 31; 83.8%) opted for CAMs, of which the majority preferred vitamins and supplements, in addition to other types of holistic therapies such as traditional Chinese, Malay and Indian treatments. This is in agreement with studies from other Asian countries including South Korea and China [12,13]. The type and prevalence of alternative therapies are highly dependent on the country [6], whereby the use of vitamins and supplements are widely reported in both Chinese (90.5%) and South Korean (46.7%) ALS patients, while a survey conducted by the German Association for Neuromuscular Diseases reported the wide usage of acupuncture (47%) and homeopathy (40%) [6].…”
Section: Discussionsupporting
confidence: 86%
“…In a study conducted in South Korea, all patients used CAM with the expectation of improvement in symptoms. However, 70.6% of the patients were not satisfied with the outcome and discontinued CAM; furthermore, only 14.5% reported intending to recommend CAM to others [ 9 ]. ALS progression is rapid and fatal.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, patients with ALS and their families can consider complementary alternative medicine (CAM) for ALS treatment. A Chinese study [ 8 ] reported that 99% of patients with ALS underwent integrative therapy (IT); moreover, a recent South Korean study [ 9 ] reported that every patient who participated in the survey received CAM treatment. In a German questionnaire study [ 10 ], 54% of patients with ALS reported having received CAM treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation